THE INFLUENCE OF INFRASTRUCTURE DEVELOPMENT ON COMMUNITY WELFARE IN HILIANA'A VILLAGE, TELUK DISTRICT IN NIAS SELATAN DISTRICT: PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA HILIANA’A KECAMATAN TELUK DALAM KABUPATEN NIAS SELATAN - Sari Dewi, Ratna; Siregar, Barham (UPMI Proceeding Series, 2023)
The title of the research is the Effect of Infrastructure Development on Community Welfare in Hiliana'a Village, Teluk Dalam District, South Nias Regency, Research Problems on the Effect of Infrastructure Development on Community Welfare in Hiliana'a Village, Teluk Dalam District, South Nias Regency. The research method in obtaining empirical data is carried out using explanatory survey method. Data collection techniques using a closed questionnaire with a Likert scale model and interviews. The population and sample of the study were 47 people. Data analysis is Product Moment Correlation Coefficient with t-test statistical.The results showed that the Infrastructure Development of Hiliana'a Village, Teluk Dalam District, South Nias Regency in the Education Infrastructure dimension had a score of 4.60, Health Infrastructure had a score of 4.51 and Clean Water and Sanitation Infrastructure had the same score of 4.42 classified as very high category, and Transportation Infrastructure is the most dominant factor in the very high category, with an average score of 4.76 in supporting community welfare. The Effect of Infrastructure Development on Community Welfare in Hiliana'a Village, Teluk Dalam District, South Nias Regency has a very strong influence of 0.763 and the proposed hypothesis is accepted, that Infrastructure Development has a large/strong influence on Community Welfare in Hiliana'a Village, Teluk Dalam District South Nias District Dimensions of Education Infrastructure, Health Infrastructure and Clean Water and Sanitation Infrastructure and Transportation Infrastructure support the welfare of the community and are the dominant factors and need to be followed up in the implementation of development in the following years in Hiliana'a Village, Teluk Dalam District, South Nias Regency.